Cryopreserving and Recovering of Human iPS Cells using Complete KnockOut Serum Replacement Feeder-Free Medium - Wagner, Kate (MyJove Corporation, 2010)
The discovery in 2006 that human and mouse fibroblasts could be reprogrammed to generate iPS cells (1-3) with qualities remarkably similar to embryonic stem cells has created a valuable new source of pluripotent cells for drug discovery, cell therapy, and basic research. GIBCO media and reagents have been at the forefront of pluripotent stem cell research for years. Knockout DMEM supplemented with Knockout Serum Replacement is the media of choice for embryonic stem cell growth and now iPS cell culture (3-9). This gold standard media system can now be used for feeder-free culture with the addition of Knockout SR Growth Factor Cocktail. Traditional human ES and iPS cell culture methods require the use of mouse or human fibroblast feeder layers, or feeder-conditioned medium. These culture methods are labor-intensive, hard to scale and it is difficult to maintain hiPS cells undifferentiated due to the undefined conditions. Invitrogen has developed Knockout SR Growth Factor Cocktail to allow you to easily transition your hiPS and hES cell cultures to feeder-free while still maintaining your use of Knockout SR.